Interactive Read Aloud and Book Selection in Primary Literacy : Pembacaan Interaktif dan Pemilihan Buku dalam Literasi Dasar Sekolah Dasar - Durriya, Tati Lathipatud; Niasari, Catur; Umar, Iin Afriyanti (Pedagogia : Jurnal Pendidikan, 2026)
General Background: Literacy competence is a national priority in Indonesian primary education under Kurikulum Merdeka, which emphasizes Capaian Pembelajaran and differentiated instruction. Specific Background: However, classroom literacy practices remain largely textbook-centered, and teachers face challenges in implementing meaningful literacy activities. Knowledge Gap: Empirical evidence is limited regarding how teachers select quality children’s books and integrate interactive read aloud with Capaian Pembelajaran. Aims: This qualitative case study examines teachers’ experiences in selecting leveled books and applying interactive read aloud in a public primary school in Depok, Indonesia. Results: Teachers demonstrated increased awareness of content relevance, student reading levels, and decodable books, yet encountered constraints in book availability and curriculum alignment. Interactive read aloud supported student engagement, subject comprehension, and reading interest while encouraging teacher reflection and preparation. Novelty: The study offers contextual insight into aligning interactive read aloud and quality book selection with Capaian Pembelajaran. Implications: Continuous professional development and improved access to diverse children’s literature are necessary to sustain primary literacy instruction. Highlights: Educators recognized the importance of aligning children’s literature with student developmental stages and curriculum outcomes. Classroom storytelling sessions encouraged active dialogue and supported subject matter understanding. Ongoing mentoring and structured preparation were identified as necessary for sustainable instructional practice. Keywords:  Interactive Reading Aloud, Literacy, Graded Books, Learning Achievements, Merdeka Curriculum.